(untitled) (Global Journal of Human-Social Science, 2015)
Family life concerns subjective and individual moments which are always unique, and constitute a part of one’s life. Therefore, it is more difficult to establish the value that is attributed to the notion of family by people in general. In order to define the value of specific, existing family environment, the quality of life of the constituents of such an environment are taken into account. Experience and the level of satisfying individual needs have a great impact on the quality of one’s family life. If a family finds itself in a deep trouble, and is unable to tackle it, then its life quality is impoverished in a significant way. The consequences of disfunctioning of a family as well as the inability to perform the tasks that a family is expected to fulfil are severe. These ramifications have a great impact on a child’s life, and the worst case scenario happens if the child is separated from its family. On the basis of the interview with a person who grew up in the orphanage, it can be concluded that despite the fact that one may have bad memories about their family, and he or she may think low of it, family is still ideologically valuable for them.